2020
DOI: 10.1056/nejmc2008646
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Covid-19 through a Citywide Pandemic Surveillance Platform

Abstract: We describe projections for the burden of infections and deaths in King and Snohomish Counties through April 7, as projections further out are strongly sensitive to assumptions about the scale of the local outbreak and importation dynamics from other regions that are not yet known. For the projections, we considered four scenarios for the increasingly effective impact of social distancing on COVID-19 incidence: • A baseline scenario assuming no change since January 15. • Scenarios with 25, 50, and 75 percent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 2 publications
2
123
0
Order By: Relevance
“…On February 29 th , 2020, a SARS-CoV-2 genome was reported (4) from a second Washington State patient, 'WA2', whose virus had been sampled on February 24th as part of a community surveillance study of respiratory viruses (5). The report's authors calculated a high probability that WA2 was a direct descendent of WA1, coming to the surprising conclusion that there had by that point already been six weeks of cryptic circulation of the virus in Washington State (4).…”
Section: Introductionmentioning
confidence: 99%
“…On February 29 th , 2020, a SARS-CoV-2 genome was reported (4) from a second Washington State patient, 'WA2', whose virus had been sampled on February 24th as part of a community surveillance study of respiratory viruses (5). The report's authors calculated a high probability that WA2 was a direct descendent of WA1, coming to the surprising conclusion that there had by that point already been six weeks of cryptic circulation of the virus in Washington State (4).…”
Section: Introductionmentioning
confidence: 99%
“…the GISAID EpiCoV database) at unprecedented speed (Elbe and Buckland-Merrett 2017;Shu and McCauley 2017; Coronaviridae Study Group of the International Committee on Taxonomy of 2020; Wu et al 2020). This has enabled the construction of molecular phylogenies that have guided our understanding of the virus transmission history, its basal mutation rate, and its potential to evade emerging therapeutics and vaccines (Bedford et al 2020;Chu et al 2020;Forster et al 2020;Kim et al 2020b;Lv et al 2020;Pachetti et al 2020;Pinto et al 2020). At the time of this writing, almost 25,000 SARS-CoV-2 genome sequences have been deposited in the GISAID EpiCoV database (www.gisaid.org) and are available through a database access agreement Buckland-Merrett 2017; Shu and McCauley 2017).…”
Section: Ryder -4mentioning
confidence: 99%
“…Although travel from China was halted by late-January, dozens of known introductions of the virus to North America occurred prior to that (Holshue et al, 2020;Kucharski et al, 2020), and dozens more known cases were imported to the US and Canada during February from Europe, the Middle East, and elsewhere. Community transmission of unknown origin was first detected in California on February 26, followed quickly by Washington State (Chu et al, 2020b), Illinois and Florida, but only on March 7 in New York City. Retrospective genomic analyses have demonstrated that case-tracing and self-quarantine efforts were effective in preventing most known imported cases from propagating (Ladner et al, 2020;Gonzalez-Reiche et al, 2020;Worobey et al, 2020), but that the eventual outbreaks on the West Coast (Worobey et al, 2020;Chu et al, 2020b;Deng et al, 2020) and New York (Gonzalez-Reiche et al, 2020) were likely seeded by unknown imports in mid-February.…”
Section: Introductionmentioning
confidence: 99%
“…Community transmission of unknown origin was first detected in California on February 26, followed quickly by Washington State (Chu et al, 2020b), Illinois and Florida, but only on March 7 in New York City. Retrospective genomic analyses have demonstrated that case-tracing and self-quarantine efforts were effective in preventing most known imported cases from propagating (Ladner et al, 2020;Gonzalez-Reiche et al, 2020;Worobey et al, 2020), but that the eventual outbreaks on the West Coast (Worobey et al, 2020;Chu et al, 2020b;Deng et al, 2020) and New York (Gonzalez-Reiche et al, 2020) were likely seeded by unknown imports in mid-February. By early March, cross-country spread was primarily due to interstate travel rather than international imports (Fauver et al, 2020).…”
Section: Introductionmentioning
confidence: 99%